Analisis Kestabilan Lereng Front IV Pit Limit Di Area Penambangan Batu Kapur PT. Semen Padang Sumatera Barat - Fuzi Atiiqah; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Semen Padang is the oldest cement factory in Indonesia which was established on March 18, 1910 under the name NV Nederlandsch Indische Portland Cement Maatschappij (NV NIPCM), which is the first cement factory in Indonesia. The activity of mining in Pit Limit Front IV development area in September 2019 occurred landslides. The landslide that occur is Toppling Failure. The actual slope is 750, the height is 20 meters, and the width is 8 meters. Based on bishop method the analysis results obtained the value of the slope safety factor (FK) in dry conditions is 1.4 with an angle of 70°, a height of 30.752 meters and a value of the Probability of Failure (PF) is 0%. the results of the analysis obtained value of the slope safety factor (FK) in saturated conditions is 1.0 with an angle of 70°, a height of 30.752 meters and a probability of failure value of 45.7%. The results of the slope design recommendations obtained the value of the slope safety factor (FK) in dry conditions is 1.9 with an angle of 66°, height of 30,752 meters and value of the probability of failure (PF) is 0%. The value of slope Safety factor (FK) in saturated condition is 1.4 with an angle 66°, height of 30.752 meters and value of the probability of failure (PF) is 0%.Keywords: Slope, Safety of Factor, Probability of Failure, Bishop Method, Topling Failure